Study of e-Health nutritional interventions on disease patients based on meta-analysis - WIDJAJA,Gunawan (2022)
Abstract Food safety means that food is non-toxic, non-hazardous, meets the nutritional requirements and does not pose any acute, subacute or chronic risks to human health. Food safety and hygiene management measures adopted by the competent authorities should be based on risk assessment. The fast proliferation of text-messaging-based mobile health (mHealth) initiatives offers a chance to enhance food quality awareness and dietary habits, especially among difficult groups. Text messaging may be used to successfully prevent or cure health problems in people and encourage good health through the use of high-quality meals. In both industrialized and developing nations, dietary practices such as frequent eating of nutrient-poor products (as unhealthy snacking) and unwillingness to consume green leafy fruit and vegetables limit micronutrient intake. In this study, we comprehensively reviewed the scientific literature on the impact of mobile health on sickness prevention control and promotion. This study focuses on the deployment of mobile health in communicable disease preventive measures, chronic illness management, and maternal healthcare to give a benchmark for mobile health intervention research in China, based on the features of existing literature.